Equipped for Migrations Across High Latitude Regions? Reduced Spur Length and Outcrossing Rate in a Biennial Halenia elliptica (Gentianaceae) With Mixed Mating System Along a Latitude Gradient - Yang, Ming-Liu; Wang, Lin-Lin; Zhang, Guo-Peng; Meng, Li-Hua; Yang, Yong-Ping; Duan, Yuan-Wen (Frontiers in Genetics, 2018)
Halenia (Gentianaceae) originated from the mountain regions of East Asia, and diversified in America following long migrations via Beringia. While H. elliptica one species of the genus in China, migrated towards high latitudes in China. Spur length of H. elliptica is highly variable. We examined the relationship between spur length and mating pattern along a latitude gradient. Field experiments were performed in two populations of H. elliptica, and we found that this species could produce seeds via both autonomous selfing and the aid of pollinators, suggesting a mixed mating system. In seven populations of H. elliptica along a latitudinal gradient, we found a trend of decrease in spur length with the increase of latitude. Based on molecular data from eleven microsatellite loci, we found that multilocus outcrossing rate decreased with the increase of latitude while the estimated inbreeding depression increased significantly, indicating that a high degree of inbreeding depression might have prevented evolution towards complete selfing in the high latitude populations with short spur length, and thus maintained mixed mating system of H. elliptica. Our results suggest that the mixed mating system of this species might be helpful in overcoming pollinator scarcity in newly colonized populations towards high latitudes after its origination in the mountain regions of China, and the decrease of spur length in the high latitude populations could result from reduced resource allocation to pollinator associated traits.